Implementasi Model Pendidikan Holistik Berbasis Karakter (PHBK) 9 Pilar Karakter Dalam Menanamkan Kemandirian Anak Usia Dini - Purnama Sari, Erlina; Imamah (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Agama Islam Universitas Nahdlatul Ulama Purwokerto, 2024)
This study aims to explore the implementation of the Character-Based Holistic Learning Model (PBHK) which focuses on the nine pillars of character in instilling an attitude of independence in early childhood at Nurul A'in Kindergarten. This research uses a descriptive qualitative method with data collection through observation, interviews, and documentation. The CBHE model aims to educate children to become individuals who are not only cognitively intelligent, but also have strong morality and independence. The nine pillars of character in the CBHE model include love of God, independence, discipline, honesty, respect, compassion, caring, fairness, and self-confidence. The implementation of CBHE in Nurul A'in Kindergarten is done through three stages: planning, implementation, and evaluation. In the planning stage, teachers compile teaching modules that include learning objectives and materials. In the implementation stage, learning is carried out every day with a gradual method: knowing feeling (Monday and Tuesday), telling a story (Wednesday and Thursday), and acting feeling (Friday) which involves various media such as storybooks and hand puppets. Evaluation is done through daily assessments categorized in developmental milestones, such as Not Yet Appearing (BM), Less Appearing (KM), Already Appearing (SM), and Consistent (K). The results show that the implementation of this model is effective in shaping children's independence, although there are challenges such as time constraints and less than optimal parental support. This study recommends close collaboration between schools and parents to ensure consistency of character education at home and at school